Growth analysis, leaf gas exchange and biochemical response of Elaeis guineensis to irrigation regimes and different sources of potassium fertilisers - Tuan Syaripah Najihah; Ibrahim, Mohd Hafiz; Nulit, Rosimah; Megat Wahab, Puteri Edaroyati (Innovative Scientific Information and Services Network, 2022)
The role of potassium in mitigating drought stress is well-established. However, studies on different sources of fertiliser to alleviate this abiotic stress in oil palm seedlings are limited. Three types of potassium fertiliser (KCl: potassium chloride, K2SO4: potassium sulphate, and KNO3: potassium nitrate) under three levels of water stress (100% ER; evapotranspiration replacement, 75% ER, and 25% ER) were exposed to 3-month-old Elaeis guineensis (oil palm) seedlings to investigate the influence of potassium source in minimising water stress effects in this crop. All treatments were arranged in Randomized Complete Block Design (RCBD) with three replications. It was found that as the level of water reduced, the Relative Growth Rate (RGR), Leaf Area Ratio (LAR), Leaf Weight Ratio (LWR), and Specific leaf area (SLA) of oil palm seedlings also reduced, but the value of Root: Shoot (R:S) improved. The result revealed that K2SO4 increased the net photosynthetic rate, transpiration rate, stomatal conductance, and Fv/Fm, as well as reduced the leaf temperature compared to KCl and KNO3. There was an interaction between water stress and the source of K on respiration rate and electrolyte leakage where K2SO4 reduced both activities. K2SO4 too reduced the proline, total phenolics, and soluble sugar by 25%, 28% and 37% respectively compared to KCL. Thus, the study has shown that water stress deteriorated the growth of oil palm seedlings while the application of K2SO4 fertiliser could minimise the effects of water stress on the leaf gas exchange and the biochemical properties of this crop.